Energy absorption performance of conical natural fiber reinforced composites Abstract - Ismail, Al Emran; Othman, Akbar (2006)
Natural fiber-reinforced composites have attracted increasing interest because of the advantages of fibers, such as low density, relatively high toughness, high strength and stiffness, good thermal properties and biodegradability. This present work used coconut coir as reinforcing tool in plastic composite. Different cone parameter and fiber volume fractions are produced and tested. The cone is compressed quasi-statically and force-displacement diagram is recorded for each case, then specific energy absorption performance is calculated and compared. It is shown that fiber volume fractions and cone parameter such vertex-angle, upper and lower diameter have controlled the cone performance. Most of the conical composites collapsed progressively under axial compressive loading.